Dihydroartemisinin Sensitizes Lung Cancer Cells to Cisplatin Treatment by Upregulating ZIP14 Expression and Inducing Ferroptosis - Zhuoying Yang; Zehao Zhou; Qingyu Meng; Zhijie Chen; Liang Yun; Jianjun Jiang; Yujing He; Meijuan Dian; Ruihao Zhang; Haotian Ge; Tianbao Yan; Biying Men; et al. (Cancer Medicine)
ABSTRACT Background Despite significant advances in lung cancer treatment, cisplatin (DDP)‐based chemotherapy remains a cornerstone for managing the disease. However, the prevalence of chemoresistance presents a major challenge, limiting its effectiveness and contributing to poor outcomes. This underscores the urgent need for novel therapeutic strategies to overcome chemoresistance and improve chemotherapy efficacy in lung cancer patients. Exploring approaches to sensitize tumors to cisplatin could enhance treatment responses and overall survival rates. Methods and Results Our study utilized a variety of lung cancer models, including cell lines, mouse models, and patient‐derived organoids, to validate the synergistic cytotoxic effects of dihydroartemisinin (DHA) and cisplatin (DDP). When combined with DDP, we demonstrate that DHA is a promising therapeutic agent that effectively triggers ferroptosis in lung cancer cells, offering a potential strategy for overcoming chemoresistance. Mechanistically, the combination of DHA and DDP synergistically enhances ZIP14 expression, modulating iron homeostasis and upregulating oxidative stress, leading to both in vitro and in vivo ferroptosis. Notably, our findings revealed that the sequential administration of DDP followed by DHA significantly increases ZIP14 expression and induces superior therapeutic outcomes compared to the simultaneous administration or DHA followed by DDP. This observation underscores the importance of the drug administration order in optimizing treatment efficacy, providing new insights into enhancing chemotherapy response in lung cancer. Conclusion Our findings suggest that combining dihydroartemisinin (DHA) with cisplatin (DDP) presents a promising strategy to overcome chemoresistance in lung cancer patients. Importantly, administering DHA during chemotherapy intervals could further optimize treatment outcomes, enhancing the overall efficacy of lung cancer chemotherapy.